Analisis Pembentukan Brand Awareness Produk Oleh-Oleh Pinyaram Nita di Nagari Titian Panjang Kecamatan 2X11 Kayutanam Kabupaten Padang Pariaman - Arizka Hamdia; Baginda Parsaulian (ARZUSIN, 2026)
The increasingly competitive traditional culinary business environment requires micro, small, and medium enterprises (MSMEs) not only to maintain product quality but also to build brand awareness among consumers. This study aimed to analyze the process of building brand awareness for Pinyaram Nita MSME and identify the level of brand awareness among local communities and passing consumers in the Titian Panjang area, 2×11 Kayutanam Subdistrict, Padang Pariaman Regency. The study employed a qualitative approach with a field research design. Informants were selected through purposive sampling and consisted of the business owner, employees, local community members, and passing consumers. Data were collected through in-depth interviews, observation, and documentation and were subsequently analyzed using the interactive model of Miles and Huberman, which comprises data reduction, data display, and conclusion drawing. The results showed that Pinyaram Nita’s brand awareness-building process had not yet been implemented optimally. Promotional activities were still dominated by word-of-mouth communication and banner placement, whereas social media had not been used consistently. The product’s visual identity, including its logo, packaging design, and distinctive brand elements, had also not been able to strengthen the business image amid competition from similar products. Brand awareness among the local community was at the brand recall level, whereas most passing consumers remained at the unaware-of-brand level; therefore, Pinyaram Nita had not yet become the primary choice when consumers sought regional specialty souvenirs. These findings confirm that the success of traditional culinary products is determined not only by taste but also by the ability to build a strong brand identity through integrated marketing communication, packaging innovation, the use of digital media, and the strengthening of consumer experience. This study contributes to the development of MSME marketing studies and provides practical implications for strengthening traditional culinary branding strategies to enhance competitiveness while supporting the preservation of local products as part of the regional creative economy.